Mechanical properties of ppnanoclay/pp and opefb/ppnanoclay/pp composites / Noorrul Wahida Abdul Razak - Abdul Razak, Noorrul Wahida (2015)
Recently, there has been a resurgence o f interest in the use of natural fibres as reinforcements in plastic for the production of low-cost and lightweight polymer composites due to their good mechanical performance and perceived environmental advantages. However, their limitations such as large scattering in mechanical properties, and insufficient understanding of mechanisms controlling their mechanical behavior and failure modes, still confine the use of natural fibre reinforced composites in non-structural applications. Hence the principal aim of this project was to achieve a better understanding of the various parameters that contribute to the mechanical properties and fracture surface, and to manipulate these parameters in order to improve and produced PPnanoclay/Polypropylene (PP) reinforced oil palm empty fruit bunch (OPEFB) composite material. Thus, in this study the oil palm empty fruit bunch fibre were used as filler and PPnanoclay/PP composite was act as the matrix material. Several characterization techniques such as tensile test, impact test, flexural test and water absorption analysis were used to assess the effect of each parameter with several numbers of OPEFB sizes (180 pm, 250 pm, 300 pm, and 355 pm). PPnanoclay/PP composites were compounded at three different PPnanoclay loading of 5 phr, 7 phr and 10 phr. From the all testing, 7 phr of PPnanoclay loading shows the best formulation composite compared to others for both PPnanoclay/PP composites and OPEFB/PPnanoclay/PP hybrid composites. Further investigation on the effects of OPEFB size in OPEFB/PPnanoclay/PP hybrid composites showed that the 355 pm size gave the most mechanical properties enhancement. The improvement due to mechanical properties and decrease of water uptake was revealed a good bonding between filler and matrix at also 355 pm. This study was also revealed that the best formulation of PPnanoclay content is at 10 phr for treated fibres of composites.